Accumulation of secreted antibodies in plant cell cultures varies according to the isotype, host species and culture conditions. Issue 4 (23rd December 2013) - Magy, Bertrand; Tollet, Jérémie; Laterre, Raphaëlle; Boutry, Marc; Navarre, Catherine
Summary Nicotiana tabacum suspension cells have been widely used to produce monoclonal antibodies, but the yield of secreted antibodies is usually low probably because of proteolytic degradation. Most IgGs that have been expressed in suspension cells have been of the human IgG1 isotype. In this study, we examined whether other isotypes displayed the same sensitivity to proteolytic degradation and whether the choice of plant host species mattered. Human serum IgG displayed different degradation profiles when incubated in spent culture medium from N. tabacum, Nicotiana benthamiana or Arabidopsis thaliana suspension cells. Zymography showed that the protease profile was host species dependent. Three human isotypes, IgG1, IgG2 and IgG4, and a mouse IgG2a were provided with the same heavy‐ and light‐chain variable regions from an anti‐human IgM antibody and expressed in N. tabacum cv. BY‐2 and A. thaliana cv. Col‐0 cells. Although all tested isotypes were detected in the extracellular medium using SDS‐PAGE and a functional ELISA, up to 10‐fold differences in the level of intact antibody were found according to the isotype expressed, to the host species and to the culture conditions. In the best combination (BY‐2 cells secreting human IgG1), we reported accumulation of more than 30 mg/L of intact antibody in culture medium. The possibility of using IgG constant regions as a scaffold to allow stable accumulation of antibodies with different variable regions was demonstrated for human IgG2 and mouse IgG2a.